Demographic Determinants of the Activity of Farms in Poland in the Acquisition of European Union Funds in the Years 2004-2006 - Rudnicki, Roman (Bulletin of Geography. Socio-economic Series, 2009)
Out of the several assistance measures of the European Union orientated towards the development of agriculture, there are two in which demographic criteria have been set for the beneficiaries, viz. support for young farmers (applications can be submitted by farmers up to 40 years old) and structural pensions (eligible farmers are of pre-retirement age: from 55 to the start of retirement age). The number of applications processed under those measures in the years 2004-2006 (the actual absorption level) as against the total number of young farmers and those of pre-retirement age (the potential absorption level) was adopted as a basis for a spatial analysis and assessment of the use of the EU funds in those fields. Indices constructed on the basis of the number of applications per 1,000 farm operators, both young and of pre-retirement age, showed there to be wide spatial differences. It was shown that the lowest activity of farms in this respect was characteristic of those in south-eastern Poland. In turn, the measures determined by the demographic structure of farmers were the most popular in the voivodeships of Kujavia-Pomerania and Wielkopolska. Such a spatial distribution contributes to a further deepening of regional disparities in Polish agriculture.